Associations between significant head injury and cognitive function, disability, and crime in adult men in prison in Scotland UK: a cross-sectional study - McMillan, Tom M.; Aslam, Hira; McGinley, Abi; Walker, Vicky; Barry, Sarah J. E. (Frontiers in Psychiatry, 2025)
BackgroundAlthough a history of head injury is common in prisoners, little is known about its impact in relation to disability and potential associations with other health problems. This is relevant to the development of effective management and interventions targeted towards health or reducing recidivism. This study investigates effects of significant head injury (SHI) on disability, cognitive function, and offending in adult male prisoners and considers relationships with common comorbidities.MethodsIn this cross-sectional study, adult male prisoners in Scotland were recruited from Her Majesty’s Prisons Low Moss and Shotts. To be included, prisoners had to be men in adult custody, fluent in English, able to participate in assessment, provide informed consent, and not have a severe acute disorder of cognition or communication. History of head injury, cognition, disability, history of abuse, health, and problematic substance use were assessed by interview and questionnaire. Comparisons were made between prisoners with and without a history of SHI.ResultsThe sample of 286 was demographically representative of approximately 8,000 adult men in prison in Scotland. Severe head injury (SHI) was found in 245/286 (86%) and was repeated over periods of time in 151/245 (62%). Disability was associated with SHI in 85/245 (35%) and was significantly associated with problematic drug or alcohol use, clinical anxiety, and clinical depression. Significant associations between SHI and cognitive test outcomes were not found. Prisoners with SHI had more arrests, charges, and convictions and at younger ages, and were at greater risk of involvement in violent and property offences.ConclusionsA history of repeated SHI is very common in adult men in prison and is associated with a greater risk of crime including violence. Disability after SHI often affects social relationships and is associated with multiple health problems. There is a need for policy and interventions to account for the “weave” of multiple health needs of people in prison, which includes history of SHI.